2010
DOI: 10.1039/c0ob00262c
|View full text |Cite
|
Sign up to set email alerts
|

Generation and amplification of optical activity of axially chiral N-(1-naphthyl)-2(1H)-pyrimidinethione by crystallization

Abstract: X-Ray crystallographic analysis of N-(1-naphthyl)-2(1H)-pyrimidinethione revealed that the space group was tetragonal and chiral P4(3). The rate of racemization due to the C-N bond rotation was considerably influenced by the solvent properties. A nonpolar solvent lowers the ΔG(‡)value by about 3.0 kcal mol(-1) relative to the value in a polar or a protic solvent. The crystallization of racemic axially chiral pyrimidinethione at high temperature led to the chiral breaking of symmetry up to 91% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
(2 reference statements)
1
18
0
Order By: Relevance
“…38,39 These complexes have achiral ligands but are chiral (denoted D or L instead of R and S) as a complex. 40 The combination of seeding and stirring gave the product with an ee of up to 91% through total spontaneous resolution. 11b).…”
Section: (4) Recent Examplesmentioning
confidence: 99%
“…38,39 These complexes have achiral ligands but are chiral (denoted D or L instead of R and S) as a complex. 40 The combination of seeding and stirring gave the product with an ee of up to 91% through total spontaneous resolution. 11b).…”
Section: (4) Recent Examplesmentioning
confidence: 99%
“…Indeed, rotational barriers are solvent-dependent, and differences enantiomerization barriers of 4.5 kJ mol À1 for 3-m-tolyl-4-tert-butylthiazoline-2-thione between isooctane and ethanol at 65.5 8C [32] and 12.5 kJ mol À1 for N-(1-naphthyl)-2(1H)-pyrimidinone between xylene and propan-1-ol at 90 8C have been reported in the literature. [33] Rotational barriers also vary with temperature depending on the value of the rotational activation entropy DS°. Experimental data and treatments of the first-order plots are reported in the Supporting Information.…”
Section: Enantiomerization Barriers In Solutionmentioning
confidence: 99%
“…In addition, this compound racemizes swiftly in apolar solvents at elevated temperatures ( t 1/2 = 4 min in xylene at 50 °C), whereas racemization at room temperature in polar solvents is negligible. 11 Racemization takes place relatively easily since it proceeds via a reversible ring-opening and closing-mechanism, 12 rather than via rotation around the chiral axis. Fujita and co-workers already showed that total spontaneous resolution can be achieved for this compound.…”
Section: Resultsmentioning
confidence: 99%